Tokopedia vs Bukalapak: Which one do you prefer? The efficacy of benefits spread - William Betan (Jurnal Ekonomi Perusahaan, 2021)
The pioneers of giant e-commerce companies in Indonesia are Tokopedia and Bukalapak. Those two marketplace have operated effectively for over five years and received positive responses from Indonesian online shoppers. The question which one has the higher benefit between the two? To answer that curiosity, the authors apply a multi-attributes approach that involves involves 14 attributes. The next question is, are the benefits spread associated positively with marketplace preference? This study aims to answer those questions. Therefore, the authors collect data using questionnaires from 100 shoppers who shop alternately in both marketplaces. The study reveals that most respondents (83%) chose Tokopedia. The remaining shoppers (17%) prefer to shop in Bukalapak. This result is consistent with Tokopedia's performance rate that higher than Bukalapak. The Chi-Square Test shows a strong inter-dependency between benefit spread and brand preference.